HUBUNGAN KEPEMIMPINAN DAN BUDAYA KERJA DENGAN DISIPLIN KERJA PEGAWAI DI SEKRETARIAT DAERAH KOTA TANGERANG - Ilal Kusnandi; Esaka Pratala (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2021)
At the Regional Secretariat of Tangerang City required good work discipline in order to coordinate the organization of other regional devices to organize the government and development in Tangerang City. The discipline of this employee requires leadership and work culture in order to achieve employee discipline in accordance with applicable laws and regulations. In this study used 3 pieces of variables of leadership, work culture and work discipline employees. To analyze the relationship between these variables used quantitative methods with associative types. As the basic ingredients of analysis used data collection tool in the form of questionnaires filled by respondents, namely the employees who work in the Regional Secretariat of Tangerang City, amounting to 84 people. The data analysis technique used is the coefficient of product moment correlation, coefficient of determination, and linear regression. The results of the study explain the positive relationship between leadership and work culture on employee performance that form linear regression equation equation of ? = 15.741 + 0.246X1 + 0.307X2. The ability of each independent variable (leadership and work culture) in influencing the dependent variable (work discipline of employees) is equal to 31.47 %. One of the suggestions in this research is that the Secretary of Regions as the highest leader in the Regional Secretariat of Tangerang City in order to pay attention to the condition of employee's work culture in receiving direction, accepting responsibility towards his work, the implementation of the work according to the task, overcoming the problems, discipline in perform tasks, team work, things that are considered can be used as a reference to evaluate the work culture of employees in the Regional Secretariat of Tangerang. In addition, the Regional Secretary is able to delegate the execution of his leadership to the structural positions he has under the leadership of the Regional Assistant, Head of Section up to the Head of Subdivision